A Two-stage Demand Response Strategy for Datacenters in the Smart Grid Environment. (July 2020) - Li, Yuling; Wang, Xiaoying; Luo, Peicong; Huang, Dingchang; Zhao, Mengmeng
Abstract: As a large load of the smart grid, datacenters usually have a huge demand for power. Datacenter participation in demand response programs of smart grids can help the grid to adjust the load while reducing its own power costs so as to save electricity costs. In this paper, we designed a two-stage demand response participation strategy to alleviate the peak load pressure of the gird and reduce the power cost of the datacenter. The first stage determines whether to participate in demand response according to the real-time electricity prices variation of the power grid and incentive information will be sent to encourage users to participate in the program to help shave the peak load. In the second stage, the datacenter interacts with its users by allowing users to submit bid information by auction. Then the datacenter selects the tasks of the winning users to postpone processing with awards, which reduces the electricity costs of the datacenter and effectively meets the demand response requirements of the smart grid. In this way, the goals of both parties could be achieved.